Improved Error Estimates of Solutions in the Linear Theory of Thin Elastic Shells - Rychter, Z. (Engineering Transactions, 1984)
DANIELSON [2] has shown that the difference between the classical linear shell theory solution and the solution of the three dimensional elasticity theory is in the L2 norm a quantity of relative order e. In this report that difference is proved to be of relative order (…), and in some cases of practical interest even (…).